Questionnaire of vasovagal reactions to blood donation in a health institution - Mejía Domínguez, Ana María; González-Hermosillo, Jesús Antonio; Valencia-Cañedo, Cesar A.; Hernández-Pacheco, Guadalupe (Horizonte Sanitario, 2022)
Objective: Identify, trough a vasovagal signs and symptoms questionnaire, blood donors in order to record the antecedents that increases the probability of presenting vasovagal reactions.Materials and Methods: A questionnaire was applied to blood donors, for three months, in the blood bank in a third-level health institution.Results: 100% of the donors answered negatively to the questions in the questionnaire, but 1.3% of them presented vasovagal reaction, with dizziness, pallor and nausea being the most frequently shown sing and symptoms. When comparing two groups with and without vasovagal reaction matched by sex, age and body mass index, there were no differences between them.Conclusions: Donors in our country are fundamentally replacement donors, so this circumstance plus their motivations should be considered for the design of surveys aimed at this population.Keywords: Vasovagal; Blood donors; Replacement